2019
DOI: 10.22161/ijaers.6.4.30
|View full text |Cite
|
Sign up to set email alerts
|

Robot Chow: Automatic Animal Feeding with Intelligent Interface to Monitor Pets

Abstract: According to the latest IBGE (Brazilian Institute of Geography and Statistics) survey, there are more than 74.3 million dogs and cats in Brazil. Moreover, the highest cost for raising these animals is pet feed, which should be served at appropriate times and quantities. In contrast, the daily lives of pet breeders have often unforeseen events such as meetings, last minute trips, traffic jams, among others. With the purpose of helping the difficulties faced by small domestic animal breeders, this work presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, one of the preventive approaches to address the feeding time and free feeding as well as health problem issue that motivates the researchers is to propose a semi-automatic or automatic pet food dispenser system, instead of manual feeding or free feeding for the convenience to pet owner. Various methods such as weight mechanism, time-based employing Arduino Uno [5], Arduino Mega [6], ESP32 [7] Raspberry Pi [8,9], have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one of the preventive approaches to address the feeding time and free feeding as well as health problem issue that motivates the researchers is to propose a semi-automatic or automatic pet food dispenser system, instead of manual feeding or free feeding for the convenience to pet owner. Various methods such as weight mechanism, time-based employing Arduino Uno [5], Arduino Mega [6], ESP32 [7] Raspberry Pi [8,9], have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that Raspberry Pi is a very flexible tool as it helps to communication with the motor driver, sensors, and motor stepper so that the food dispenses when the pet approaches. As the food dispenser in [5][6][7][8][9][10] requires only Alternating Current (AC) or Direct Current (DC) power, it is inoperable when there is no energy supply. All these issues can be resolved with the use of an autonomous pet food dispenser and a solar-powered system to promote and sustainable environment.…”
Section: Introductionmentioning
confidence: 99%